Vibração incidente sobre o corpo inteiro do operador de trator agrícola ensaiado em pista de vibração com diferentes lastros, velocidades e pressões de inflação dos pneus - Sandi, Jefferson [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
One of the main variables that affect the productive performance of operators of agricultural tractors and can cause serious health problems is the vibration generated during the operation of the machine. This work aimed to evaluate the vibration that affects the whole body of the operator through the seat of a farm tractor in a standardized vibration track test. It was used a 92 kW tractor with four conditions of ballasting: full weight, employing only solid ballast, only liquid ballast and completely without ballast, in four speeds of displacement: 1.19 m s-1; 1.47 m s-1; 1.75 m s-1 and 2.08 m s-1, and three combinations of inflation pressures in the rear and front axle, respectively: 82.73 kPa and 110.31 kPa; 110.31 kPa and 137,85 kPa and 137.85 kPa and 165.47 kPa. It was utilized a three-axis accelerometer (x, y, and z axes), fixed on the tractor seat for evaluation of the effect of vibration on the whole body of the operator. The acquisition was made with HVM-100 and software BLAZE ® 6.1.1, being obtained the average acceleration parameters, maximum and minimum acceleration, vibration dose value, the crest factor and the dose projection to 8 hours of work. It was realized the analysis of variance and average separation for all components analysed, and analysis of major components for the values of average acceleration and vibration dose value. All the statistical analyses were made with Tukey test at 5% probability (p < 0.05). Combinations of tire inflation pressures doesn't affected the values of vibration that occured on whole body of the operator. The speed was the factor that showed greater influence on vibration of the whole body of the operator, where the smallest tractor displacement speed resulted in the best scenarios. The maximum ballast presented the best scenarios for the operator when combined with the lower speed. For the vibration dose value was not found values above the ...

Uma das principais variáveis que afetam o rendimento produtivo dos operadores de tratores agrícolas que podem causar sérios problemas de saúde é a vibração gerada durante o funcionamento dessa máquina. Este trabalho teve como objetivo avaliar a vibração que incide sobre o corpo inteiro do operador através do assento de um trator agrícola mediante ensaio em pista de vibração padronizada. Empregou-se um trator de 92 kW de potência em quatro condições de lastragem: completamente lastrado, empregando somente lastro sólido, somente lastro líquido e completamente sem lastros, em quatro velocidades de deslocamento: 1,19 m s-1; 1,47 m s-1; 1,75 m s-1 e 2,08 m s-1, três combinações de pressões de inflação nos rodados traseiros e dianteiros, respectivamente: 82,73 kPa e 110,31 kPa; 110,31 kPa e 137,85 kPa e 137,85 kPa e 165,47 kPa. Utilizou-se um acelerômetro de três eixos (eixos x, y e z), fixado sobre o assento do trator para avaliação do efeito da vibração no corpo do operador. A aquisição foi feita com o aparelho HVM - 100 e software BLAZE® 6.1.1, sendo obtidos os parâmetros de acelerações média, máxima e mínima, pico máximo de aceleração, valor da dose de vibração, o fator de crista e a projeção de dose para 8 horas de trabalho. Realizou-se a análise de variância e separação de médias para todos os componentes analisados e a análise de componentes principais para as medições de aceleração média e valor da dose de vibração. Todas as análises estatísticas foram feitas com o teste de Tukey a 5% de probabilidade (p<0,05). As combinações de pressões de inflação dos pneus não afetaram os valores de vibração que incidiram sobre ...
Vibration incident on whole body of operator of agricultural tractor tested in a vibration track with different weights, speeds and pressures from inflation of tires
Keywords: Mecanização agrícola; Máquinas agrícolas; Segurança do trabalho; Engenharia humana; Insalubridade; Farm mechanization